Peningkatan Keterampilan Berpikir Kritis melalui Pendekatan Kontekstual Berbantukan Montase pada Materi Budaya Daerah Kelas V UPT SDN 274 Gresik - Naila Nisyyah Fanni; Arya Setya Nugroho; Afakhrul Masub Bachtiar (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2026)
This research purposes to improve the critical thinking skills of fifth-grade students at UPT SDN 274 Gresik regarding local culture for the 2024/2025 academic year. The methodology used is classroom action research. Data collection techniques were conducted through tests to assess students’ critical thinking skills and observations to assess student and teacher activities. The data analysis used included calculating the average scores from the tests and the results of the observations. The sample used in this research comprised of fifth-grade students at UPT SDN 274 Gresik during the 2024/2025 academic year. The results of the research indicate that the average score on the critical thinking skills test increased from 50.36 in the pre-action phase to 67.14 in Cycle I, and reached 86.43 in Cycle II. The findings of the teacher activity observations displayed an increase from 3.89 in Cycle I to 4.00 in Cycle II. The average results of student activity observations also increased from 68.21 in Cycle I to 86.43 in Cycle II. These results lead to the conclusion that the contextual approach proved effective in improving students’ critical thinking skills regarding local cultural material.